Circle‐Seq reveals genomic and disease‐specific hallmarks in urinary cell‐free extrachromosomal circular DNAs. Issue 4 (26th April 2022) - Lv, Wei; Pan, Xiaoguang; Han, Peng; Wang, Ziyu; Feng, Weijia; Xing, Xue; Wang, Qingqing; Qu, Kunli; Zeng, Yuchen; Zhang, Cailin; Xu, Zhe; Li, Yi; et al.
Abstract: Background: Extrachromosomal circular deoxyribonucleic acid (eccDNA) is evolving as a valuable biomarker, while little is known about its presence in urine. Methods: Here, we report the discovery and analysis of urinary cell‐free eccDNAs (ucf‐eccDNAs) in healthy controls and patients with advanced chronic kidney disease (CKD) by Circle‐Seq. Results: Millions of unique ucf‐eccDNAs were identified and comprehensively characterised. The ucf‐eccDNAs are GC‐rich. Most ucf‐eccDNAs are less than 1000 bp and are enriched in four pronounced peaks at 207, 358, 553 and 732 bp. Analysis of the genomic distribution of ucf‐eccDNAs shows that eccDNAs are found on all chromosomes but enriched on chromosomes 17, 19 and 20 with a high density of protein‐coding genes, CpG islands, short interspersed transposable elements (SINEs) and simple repeat elements. Analysis of eccDNA junction sequences further suggests that microhomology and palindromic repeats might be involved in eccDNA formation. The ucf‐eccDNAs in CKD patients are significantly higher than those in healthy controls. Moreover, eccDNA with miRNA genes is highly enriched in CKD ucf‐eccDNA. Conclusions: This work discovers and provides the first deep characterisation of ucf‐eccDNAs and suggests ucf‐eccDNA as a valuable noninnvasive biomarker for urogenital disorder diagnosis and monitoring. Abstract : Urinary cell‐free extrachromosomal circular DNA (ucf‐eccDNA) is common in humans. Ucf‐eccDNAs are less than 1000 bp, high in GC content and frequently derived from gene‐rich regions, short interspersed transposable elements (SINEs) and simple repeat elements. Patients with advanced chronic kidney diseases (CKDs) have higher ucf‐eccDNA. Enrichment of the miRNA gene ucf‐eccDNAs is observed in CKD patients.